Domestic Violence and Postpartum Depression - Winnellia Fridina Sandy; Djaswadi Dasuki; Elli Nur Hayati; Suhariyanto Suhariyanto (Jurnal Ners, 2020)
Introduction: Domestic violence occurs at all levels of society. Evidence shows that sexual, physical and psychological violence are predisposing factors of postpartum depression. This study was aimed to determine the relationship between domestic violence and postpartum depression.Methods: This research adopted quantitative method through observational with a cross-sectional study design by analyzing secondary data from SEHATI longitudinal surveillance. A total of 232 women was selected as sample  using a purposive sampling method, with the sample criterion being mothers with children <2 years old located in Purworejo District, Central Java, consisting of 16 sub-districts and 494 villages. The data   obtained were analyzed using the chi square statistical test and binomial regression test.Results: The results of the quantitative data showed that physical violence against postpartum depression (PR = 1.7; 95% CI = 1.23-2.38), psychic violence against postpartum depression (PR = 1.9; 95% CI = 1.44-2.54), and sexual violence against postpartum depression (PR-2.0; 95% CI = 1.54-2.65). The result of the qualitative data showed that postpartum depression occurred due to domestic violence.Conclusion: Physical, psychological and sexual violence in the household are significantly related to postpartum depression.